2006
DOI: 10.1085/jgp.200509456
|View full text |Cite
|
Sign up to set email alerts
|

Mini-dystrophin Expression Down-regulates Overactivation of G Protein–mediated IP3 Signaling Pathway in Dystrophin-deficient Muscle Cells

Abstract: We present here evidence for the enhancement of an inositol 1,4,5-trisphosphate (IP3) mediated calcium signaling pathway in myotubes from dystrophin-deficient cell lines (SolC1(−)) as compared to a cell line from the same origin but transfected with mini-dystrophin (SolD(+)). With confocal microscopy, we demonstrated that calcium rise, induced by the perifusion of a solution containing a high potassium concentration, was higher in SolC1(−) than in SolD(+) myotubes. The analysis of amplitude and kinetics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
34
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 42 publications
(50 reference statements)
5
34
0
Order By: Relevance
“…Our previous works strongly supported the hypothesis of an overactivation of Ca 2ϩ release in dystrophin-deficient cells, both during membrane depolarization (4) and, at rest, through spontaneous Ca 2ϩ release events (5). Previous studies from other groups have provided evidence for at least two phases in the calcium rise observed in cultured skeletal muscle cells exposed to a high potassium solution (27,40).…”
supporting
confidence: 83%
“…Our previous works strongly supported the hypothesis of an overactivation of Ca 2ϩ release in dystrophin-deficient cells, both during membrane depolarization (4) and, at rest, through spontaneous Ca 2ϩ release events (5). Previous studies from other groups have provided evidence for at least two phases in the calcium rise observed in cultured skeletal muscle cells exposed to a high potassium solution (27,40).…”
supporting
confidence: 83%
“…We recently found that both expression and localization of IP 3 Rs are different in normal and dystrophic human skeletal muscle and cell lines (Cárdenas et al 2010). On the other hand, experiments performed using two types of myotubes originated from the same Sol8 cell line -dystrophin deficient myotubes, SolC1(-), and myotubes transfected to express the minidystrophin, SolD(+) -show that Ca 2+ rise evoked by potassium depolarization was higher in SolC1(-) than in SolD(+) myotubes (Balghi et al 2006a). Analysis of the kinetics of the Ca 2+ rise, reveals that the slow IP 3 -dependent release may be increased in the SolC1(-) as compared to the SolD(+), suggesting an inhibitory effect of mini-dystrophin on IP 3 R-dependent K + -evoked Ca 2+ release (Balghi et al 2006a).…”
Section: Alterations In Both Ip 3 Rs and E-t Coupling In Dmd Modelsmentioning
confidence: 98%
“…Analysis of the kinetics of the Ca 2+ rise, reveals that the slow IP 3 -dependent release may be increased in the SolC1(-) as compared to the SolD(+), suggesting an inhibitory effect of mini-dystrophin on IP 3 R-dependent K + -evoked Ca 2+ release (Balghi et al 2006a). Moreover, it has been described that IP 3 production after membrane depolarization is significantly elevated in dystrophin-deficient myotubes and that the presence of minidystrophin under the membrane leads to reduced IP 3 production (Balghi et al 2006a). In fact, we have recently demonstrated, using normal (RCMH) and dystrophic (RCDMD) human skeletal muscle cell lines, that IP 3 dependent, slow Ca 2+ transients evoked by electrical stimulation are faster in dystrophic cells, compared to normal myotubes (Cárdenas et al 2010).…”
Section: Alterations In Both Ip 3 Rs and E-t Coupling In Dmd Modelsmentioning
confidence: 99%
See 2 more Smart Citations